A dual role for the cAMP-dependent protein kinase in tyrosine hydroxylase gene expression. - Kim, K S (1993)
Tyrosine hydroxylase (TH) catalyzes the conversion of L-tyrosine to 3,4-dihydroxy-L-phenylalanine, the first and rate-limiting step in catecholamine biosynthesis. The cAMP-dependent protein kinase (PKA) phosphorylates and activates the TH enzyme and is thought to mediate transcriptional induction of the TH gene. To better understand the functional role of PKA in TH gene regulation, we studied TH gene expression at the transcriptional, translational, and post-translational levels in several PKA-deficient cell lines derived from rat PC12 pheochromocytoma cells. Strikingly, all PKA-deficient cell lines analyzed in this study showed substantial deficits in basal TH expression as measured by TH enzymatic activity, level of TH immunoreactivity, TH protein level, and steady-state mRNA level. Interestingly, the steady-state level of mRNA correlated well with levels of TH activity, immunoreactivity, and protein. In addition, PKA-deficient cell lines lacked transcriptional induction of the TH gene following treatment with dibutyryl cAMP. Cotransfection of PKA-deficient cells with an expression plasmid for the catalytic subunit of PKA fully reversed transcriptional defect, as indicated by robust transcriptional induction of a reporter construct containing 2400 bp of TH upstream sequence in all PC12 cells tested. These data indicate that the PKA system regulates both the basal and the cAMP-inducible expression of the TH gene primarily at the transcriptional level in PC12 cells.